(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
The article is an autobiographical account of a theater artist who sees herself as a “theatrical nomad.” She narrates her journey from childhood in Romania, where she was influenced by puppet theater, to her studies in Prague, where she deepened her connection with animated forms theater. Back in Romania, she performed under the communist regime, using metaphors to circumvent censorship. Later, she traveled to the United States and other countries with her performances and, for love, eventually moved to the U.S. and later to Geneva. Throughout the text, she reflects on her artistic vocation, the social impact of theater, and her choice to live as an itinerant artist, dedicated to creating plays that meaningfully touch both children and adults.